Gender dimensions of alcohol consumption and alcohol-related problems in Latin America and the Caribbean - Pyne, Hnin Hnin (World Bank discussion papers, 2002)
While the World Bank has included the issue of alcohol consumption and production on its' agenda for the past ten years, it has not included gender dimensions in the issue. By focusing on alcohol consumption in Latin America and the Caribbean, the instances of death, disease and domestic violence arising from alcoholism were tracked. This study recommends an approach to dealing with the damage done by alcohol consumption and production that goes beyond controlling its' availability. Specifically the measures recommended include: increasing knowledge through research; developing indicators to measure consumption levels and patterns among men and women, and the economic and social consequence of alcohol use; integrating the issue of alcohol use and related problems into consultations with governments and civil society organizations; and investment lending where appropriate, to address the issue.